A Semiotic Analysis on Morris Lifestyle Advertisement - Tausya, Resi Syahrani; Muchtar, Muhizar; Perangin-Angin, Alemina Br. (RADIANT: Journal of Applied, Social, and Education Studies, 2022)
This research aimed to analyse about the signs contained in marketing advertisements of Morris Lifestyle, as well as the meaning of the sign through the symbolic relation between the signifier and the signified. This research applied a qualitative descriptive method with the data source is Morris Lifestyle advertisement video, and the data used in this study are text, images and sound. The findings of this research consist of signs found in advertisements. There are thirteen signs found in the advertisement, for example; Creative, Woman expression, Stylish, Adventure, Manly, Metropolis, Big, Freedom, Long Lasting, Independent, I Want More, Vintage, and Approved 100% Kamu Ganteng. The findings of this study are expected to be a useful resource in other research and for the development of semiotic studies towards commercial work.